OXYGEN AND CARBON ISOTOPIC COMPOSITIONS OF CARBONATITE-LIKE ROCKS IN THE TUNGUSKA SYNECLISE - Kudryavtsev D.I.; Pokrovskii B.G.; Vrublevskii V.V.; Parnachev V.P.; Sapronov N.L.; Moskalev V.A. (My University, 2001)
Mineral, chemical, and isotopic (C, O) compositions were studied in carbonatite-like rocks from 11 areas in the Nizhnyaya and the Podkamennaya Tunguska drainage basins. Based on the internal structures and mineral compositions of the rocks, they were classified into the following two varieties: (1) coarse- and medium-crystalline olivine-magnetite-calcite rocks with elements of miarolitic and orbicular structures and (2) fine-grained calcitic rocks with a banded distribution of magnetite, hematite, and fluorite. The rocks of the first variety showed a fairly monotonous carbon isotopic composition (δ13C = -1.8±0.3‰), similar to the composition of the surrounding sedimentary carbonates, and high values of δ18O (16.6±2.0‰), similar to those in hydrothermal rocks. The rocks of the second variety yielded a notably lighter isotopic composition of carbon (δ13C = -4.6±1.8) and oxygen (δ18O = 14.2±2.6), which showed a rough positive correlation. The fractionation of oxygen isotopes between the calcite and magnetite coexisting in the studied carbonatite-like rocks defined the equilibration temperatures ranging between 400 and 1000°C. However no high-temperature minerals, typomorphic for carbonatites, were found in them, their contents of trace elements (Sr, Zr, and Nb) being comparable with those in sedimentary carbonates. The results of this study suggest that the carbonatite-like rocks were produced by thermal solutions, whose salt contents were controlled by interaction with the surrounding sedimentary carbonates and, to a lesser extent, by the rocks of a flood-basalt association. In places, the hydrothermal (and possibly sedimentary) carbonate rocks seem to have experienced partial melting under the impact of flood-basalt intrusions, which resulted in the formation of peculiar orbicular structures. A genetic association of the carbonatite-like rocks from the Tunguska syneclise with alkali ultramafic magmas seems to be scarcely probable.
Keywords: Tunguska syneclise; Isotopic compositions